Pendampingan Penyusunan Laporan Keuangan untuk UMKM Binaan Yayasan Dharma Bhakti Muslim Indonesia (YDBMI) - Setyawan, Hendri; Chrisna Suhendi (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
Micro, Small and Medium Enterprises (MSMEs) are recognized as the backbone of the national economy in many countries, including Indonesia. Even so, there are problems related to financial management, especially accounting records. Orderly accounting records will lead to financial reports that are relevant and reliable for decision making by various parties. Technological advances accompanied by the widespread use of gadgets such as cell phones have opened opportunities for the use of accounting technology in the form of android applications that are operated by cell phones. Of the various applications on the market, the “Si Apik” application was chosen. This application was developed by Bank Indonesia. This community service aims to provide assistance in the use of Android-based accounting applications for the preparation of MSME financial reports. The target group of MSMEs are those under the guidance of the Indonesian Muslim Dharma Bhakti Foundation (YDBMI). The series of mentoring activities consists of pre-activities, motivational materials on financial management, accounting basics and the practice of inputting “Si Apik” application data.